2018
DOI: 10.1186/s13223-018-0251-z
|View full text |Cite
|
Sign up to set email alerts
|

A population-based epidemiological study of anaphylaxis using national big data in Korea: trends in age-specific prevalence and epinephrine use in 2010–2014

Abstract: BackgroundPrevious reports on anaphylaxis in Asia are limited to relatively small-scale studies. We performed this study to identify the nationwide prevalence of anaphylaxis and epinephrine prescription rates by age groups.MethodsThe total number of patients, yearly and overall prevalence, percentage of emergency department visits, and epinephrine prescription rates were calculated for patients diagnosed with anaphylaxis based on the Korean National Health Insurance database from 2010 to 2014.ResultsThe mean p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
3
14
1
Order By: Relevance
“…A recent population-based study from Korea also documented a 1.9-fold increase in the prevalence of anaphylaxis. 52 These Asian data suggest at least a 2-fold rise in anaphylaxis incidence rate in the past 20 years, which is similar to the reported data from the West. A 1.89-fold (89%) increase in the incidence of hospital admissions for anaphylaxis, from 1.35 to 2.38 per 100 000 person-years, between 1998 and 2011 in Spain, was reported, 53 for which the greatest increase was in food-induced anaphylaxis in the 0-to 14-year age group.…”
Section: How Are the Anaphylaxis Trends Changing Over Time In The Esupporting
confidence: 87%
See 2 more Smart Citations
“…A recent population-based study from Korea also documented a 1.9-fold increase in the prevalence of anaphylaxis. 52 These Asian data suggest at least a 2-fold rise in anaphylaxis incidence rate in the past 20 years, which is similar to the reported data from the West. A 1.89-fold (89%) increase in the incidence of hospital admissions for anaphylaxis, from 1.35 to 2.38 per 100 000 person-years, between 1998 and 2011 in Spain, was reported, 53 for which the greatest increase was in food-induced anaphylaxis in the 0-to 14-year age group.…”
Section: How Are the Anaphylaxis Trends Changing Over Time In The Esupporting
confidence: 87%
“…The largest increase in this study was seen in the 0‐ to 9‐year‐old age group (4.1‐19.7 per 100 000 person‐years) but it was not reported whether this increase could be attributed to food anaphylaxis. A recent population‐based study from Korea also documented a 1.9‐fold increase in the prevalence of anaphylaxis . These Asian data suggest at least a 2‐fold rise in anaphylaxis incidence rate in the past 20 years, which is similar to the reported data from the West.…”
Section: Anaphylaxis Triggers—east Vs Westsupporting
confidence: 77%
See 1 more Smart Citation
“…[15,21] Present study also showed the increase of ED visits for anaphylaxis in Korea, which is consistent with previous reports that prevalence rates of anaphylaxis have increased in recent years worldwide, [3,2225] and in Korea. [26,27] Although it may need more studies to understand the reason why incidence of anaphylaxis increase, changes in environments and lifestyle, and increase of awareness about anaphylaxis might be one of the reasons for increase ED visits for anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, previous anaphylaxis studies were mostly retrospective medical chart reviews focusing on specific age groups, either children or adults. 12 , 13 Recent big data analyses on anaphylaxis are useful in investigating the epidemiology or trends over a period of time; 14 , 15 however, limitations exist as some factors such as eliciting triggers, severity, or treatment cannot be identified through the national big data. Hence, we developed a multicenter web-based registry to investigate the triggers, clinical features, and treatment details of anaphylaxis in Korean patients, including all age groups.…”
Section: Introductionmentioning
confidence: 99%